Persistence of contamination of hens' egg albumen in vitro with Salmonella serotypes. - Lock, J. L. (Cambridge University Press, 1992)
A study was made of the persistence of different Salmonella serotypes in hens' egg albumin in vitro at 4, 20 and 30 degrees C. The majority of serotypes remained viable but did not increase in numbers at 20 and 30 degrees C for 42 days. At 4 degrees C many of the serotypes died out. The addition of ferric ammonium citrate on the 42nd day of incubation induced multiplication of organisms incubated at 20 and 30 degrees C, but not at 4 degrees C. The pH and glucose concentration of the albumen diminished only when heavy growth occurred. Salmonella enteritidis remained viable on the air cell membrane in vitro for 17 days at 4, 20 and 30 degrees C. Thirty percent of the organisms also remained motile in albumen for 42 days at 25 degrees C and up to 5% of the cells remained motile for up to 20 days at 4 degrees C.